Novel c.191C>G (p.Pro64Arg) MPV17 mutation identified in two pairs of unrelated Polish siblings with mitochondrial hepatoencephalopathy. (28th July 2013) - Piekutowska-Abramczuk, D.; Pronicki, M.; Strawa, K.; Karkucińska‐Więckowska, A.; Szymańska‐Dębińska, T.; Fidziańska, A.; Więckowski, M.R.; Jurkiewicz, D.; Ciara, E.; Jankowska, I.; Sykut‐Cegielska, J.; Krajewska‐Walasek, M.; et al.
<x xml:space="preserve">Abstract</x> This study reports clinical, biochemical and histopathological findings associated with a novel homozygous MPV17 mutation in four patients with mitochondrial depletion syndrome. The severe course of the disease, which started in the first weeks of life, was dominated by a failure to thrive, hypotonia and liver dysfunction, with relatively mild neurological involvement. All affected infants died by 1 year of age. Laboratory findings included progressive liver failure (hypertransaminasaemia, icterus, and coagulopathy), recurrent hypoglycaemia, lactic acidaemia, hyperferritinaemia, and increased transferrin saturation. Histological and ultrastructural analyses uncovered significant lipid accumulation in hepatocytes and myocytes. A severe decrease in the mitochondrial/nuclear DNA (mtDNA/nDNA) ratio was found post‐mortem in the livers (and in one muscle specimen) of both examined patients. Oxidative phosphorylation system (OXPHOS) Western blotting revealed low levels of complexes I, III and IV subunits. The highlights of our findings are as follows: (i) The novel p.Pro64Arg mutation is the second recurrent MPV17 mutation reported. The phenotype associated with the p.Pro64Arg mutation differs from the phenotype of the relatively common p.Arg50Gln mutation, suggesting the existence of a genotype–phenotype correlation. (ii) Tissues collected from patients during autopsy may be useful for both mtDNA/nDNA ratio assessment and OXPHOS Western blotting.